The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/nu13041263
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens Extracts Enhance DNA Repair Response in UVB Damaged HaCaT Cells

Abstract: Physiological processes in skin are associated with exposure to UV light and are essential for skin maintenance and regeneration. Here, we investigated whether the leaf and callus extracts of Perilla frutescens (Perilla), a well-known Asian herb, affect DNA damage response and repair in skin and keratinocytes exposed to Untraviolet B (UVB) light. First, we examined the protective effects of Perilla leaf extracts in UVB damaged mouse skin in vivo. Second, we cultured calluses using plant tissue culture technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…It was reported that UVB with a dose of 30 mJ/cm 2 begins to destroy the stability of intracellular DNA, inhibit DNA synthesis, and reduce the vitality of HaCaT cells. , Furthermore, based on the minimum erythema dose (MED) of 20 mJ/cm 2 , 22 MED (440 mJ/cm 2 ) was recorded as the maximum daily UVB dose . To study the mechanism of skin injury caused by daily UVB irradiation, the maximum irradiation dose in this study was set at 480 mJ/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that UVB with a dose of 30 mJ/cm 2 begins to destroy the stability of intracellular DNA, inhibit DNA synthesis, and reduce the vitality of HaCaT cells. , Furthermore, based on the minimum erythema dose (MED) of 20 mJ/cm 2 , 22 MED (440 mJ/cm 2 ) was recorded as the maximum daily UVB dose . To study the mechanism of skin injury caused by daily UVB irradiation, the maximum irradiation dose in this study was set at 480 mJ/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As reported, the repair program of DNA started once the cell cycle detection system sensed abnormal structures of chromosomes and DNA. 9,33 During the process of DNA repair, the transformation of unrepaired CPD damage into DNA breakage might be one of the main causes of UVB-mediated cytotoxicity. 7 Under the high dose of UVB radiation, the defects in the repair process of DNA double-strand breaks may damage the stability of chromosomes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They inhibit microbial growth and have antioxidative, anti-inflammatory and anti-aging properties [10] (Table 1). Tomatoes, watermelons, red peppers, papayas, apricots, pink grapefruit [24,25] Perilla frutescens is rich in antioxidant substances such as polyphenols, which can repair the DNA damage and keratinocytes in the skin exposed to UVB light, and has the effects of antioxidation, anti-inflammation and anti-allergy [26]. Cinnamaldehyde (CIN), the main component of cinnamon, also has strong antioxidant activity [27].…”
Section: Plant Antioxidantsmentioning
confidence: 99%
“…The herb has been traditionally used in folk medicine for the treatment of colds, cough, asthma, vomiting, stomach disorders, depression, intoxications with seafood and allergic reactions ( Fujiwara et al, 2018 , Ahmed and Tavaszi-Sarosi, 2019 ). The bioactivity of perilla is widely studied and found that it has antioxidant, antimicrobial, antidepressive, anxiolytic, chemopreventive and antitumor, anti-inflammatory activities ( Banno et al, 2004 , Osakabe et al, 2004 , Park et al, 2010 ), anti-allergic effects ( Yang et al, 2021 ), keratinocyte ageing prevention ( Lee and Park, 2021 ), hyperpigmentation diseases of skin and ageing ( Mungmai et al, 2020 ). A recent study, for the first time, indicates that perilla leaf extracts (PLE) are able to limit the replication of SARS-CoV-2 by disabling the virion.…”
Section: Introductionmentioning
confidence: 99%